Seismic Vulnerability Analysis of Steel Clarification Tank - Chuyun Cheng; Xiwei Cheng; Wanlin Zhang; Xinhai Zhou; Junliang Hong; Xuansheng Cheng (Shock and Vibration, 2023)
As a physical analysis method, susceptibility not only predicts the probability of failure of a structure under different hazard levels but also prevents disasters induced by structural damage due to vulnerable members. To study the susceptibility of steel clarification tank under earthquake action, this study analyzes the dynamic response of steel clarification tank under near-field impulse, near-field no impulse, and far-field ground shaking, derives IDA curve clusters by incremental dynamic analysis method, and conducts related studies to analyze the susceptibility of clarification tank structures through susceptibility curves. The results of the study show that the probability of failure of the clarification tank under different ground shaking intensities is different. The probability of liquid wave height transcendence of the clarification tank under seismic action is the largest, the probability of liquid wave height transcendence of the clarification tank under near-field pulsed seismic action is the second, the probability of liquid wave height transcendence of the clarification tank under near-field nonpulsed seismic action is the smallest, and the probability of transcendence occurs similarly in near-field pulsed and far-field seismic actions.